Antibacterial Activity and Anti-Biofilm Formation of Henna (Lawsonia inermis) Extracts against Pseudomonas aeruginosa - Lattab, Aicha; Djibaoui, Rachid; Arabi, Abed (My University, 2017)
Pseudomonas aeruginosa is an opportunistic bacterium causing severs nosocomial infections. It is characterized by its ability to form attached biofilm to protect itself from various external pressures. These adherent cells of P. aeruginosa make treatment of their infections complicated and demand new therapies. The present work was focused on the study of L. inermis extracts effects on planktonic cells and on biofilm formation by seven strains of P. aeruginosa. The henna plant was harvested from two different regions in Algeria: Adrar and Biskra. Two solvents were used to extract L. inermis flavonoids compounds. The ethyl acetate and butanolic fractions were prepared from a hydro-methanolic extract (70%). The results show that all studied extracts present an antibacterial properties against all the isolates tested. It was also indicated that L. inermis of Adrar had the highest anti- P. aeruginosa activity compared with henna of Biskra. However the butanolic fractions of both L. inermis samples have the highest effect with a MIC of 3.12mg/ml and 6.25mg/ml for samples of Adrar and Biskra respectively, compared with the fractions of ethyl acetate which showed a MIC of 6.25mg/ml and 12.5mg/ml for the same samples. Also, the biofilm formation was decreased when incubated with the ½ MIC of butanolic fraction for both L. inermis tested. Whereas the ½ MIC of ethyl acetate extracts did not affect biofilm formation in all isolates of P. aeruginosa. The quantitative estimation showed that ethyl acetate extracts for both varieties of L. inermis are rich in polyphenols (224,83-136,95 mg GAE/g) and flavonoids (20,15-24,92 mg QE/g) compared to butanolic extracts. Finally we can conclude that extraction by butanol makes it possible to better concentrate the antibacterial active ingredients present in the hydromethanolic extract of L. inermis leaves
Keywords: Pseudomonas aeruginosa, Lawsonia inermis, Antibacterial activity, MIC, MBC, Biofilm.